Loose-fit polypseudorotaxanes constructed from γ-CDs and PHEMA-PPG-PEG-PPG-PHEMA - Kong, Tao; Ye, Lin; Zhang, Ai-ying; Feng, Zeng-guo (Beilstein Journal of Organic Chemistry, 2014)
A pentablock copolymer was prepared via the atom transfer radical polymerization of 2-hydroxyethyl methacrylate (HEMA) initiated by 2-bromoisobutyryl end-capped PPO-PEO-PPO as a macroinitiator in DMF. Attaching PHEMA blocks altered the self-assembly process of the pentablock copolymer with γ-CDs in aqueous solution. Before attaching the PHEMA, the macroinitiator was preferentially bent to pass through the inner cavity of γ-CDs to give rise to tight-fit double-chain stranded polypseudorotaxanes (PPRs). After attaching the PHEMA, the resulting pentablock copolymer was single-chain stranded into the interior of γ-CDs to form more stable, loose-fit PPRs. The results of 1H NMR, WXRD, DSC, TGA, 13C CP/MAS NMR and FTIR analyses indicated that γ-CDs can accommodate and slip over PHEMA blocks to randomly distribute along the entire pentablock copolymer chain. This results in unique, single-chain stranded PPRs showing no characteristic channel-type crystal structure.
Keywords: block copolymer; γ-CD; loose-fit; poly(2-hydroxyethyl methacrylate); polypseudorotaxane